Designing a student financial management mobile application using personal extreme programming method - Jaka Pratama, Moh Alfrizal Septian; Tri Hidayat, Ahmad (Universitas Trunojoyo Madura, 2025)
Managing finances effectively is a common challenge frequently faced by university students. Difficulties in managing finances are often caused by a lack of understanding of income and expenses, making it difficult for many students to save or create a proper budget. This study aims to develop a mobile application to help students manage their monthly finances. The application is expected to assist students in understanding their financial condition and making wiser financial decisions. It is designed for the Android platform using the Dart programming language, which is known for its flexibility and strong community support. The Personal Extreme Programming (PXP) approach was chosen as the development method due to its adaptive nature and ability to respond quickly to changing requirements, in line with the dynamic nature of the tech world. The application includes key features such as daily income and expense tracking, transaction categorization, and financial reports presented in an easy-to-understand visual format. Students can utilize these features to monitor their finances in a structured manner. Based on the results of black box testing, all of the application's main features performed as expected, with a 100% success rate. Meanwhile, usability testing involving 20 student respondents showed an average user satisfaction score of 4.3 out of 5, with 92% of respondents stating that the visualization feature was very helpful in understanding spending patterns. This research contributes to student financial management and demonstrates the effectiveness of the PXP method in developing mobile applications to solve real-world problems.Keywords: Android, Mobile Application, Financial Management, Students, Personal Extreme Programming.